Variation of Agitator Blades in Continous Settling Tank to Reduce Oil Losses in Oil Refining Process in Palm Palm Factories - Darmadi, Herry; Mustakim, Mustakim; Irwansyah; Wawuru, James Van Alex; Ginting, Maulidna; Prasetya, Agil Bagus (LPPM Politeknik Aceh Selatan, 2024)
Continuou Settling Tank (CST) is one of the units located at the clarification station where the CST works to separate oil and mud based on differences in specific gravity where the lighter density will go up, namely oil, while the heavy type will settle to the bottom, namely mud. The language here is how to make the construction of the agitator transmission in the Continuou Settling Tank (CST) unit and how the agitator blade influences the oil content contained in the sludge in the Continuou Settling Tank (CST) unit. The method is carried out with variations in the number of blades that open 2, 4 and 6 pieces. The specifications of the equipment data obtained are primary data resulting from the design of the Continuou Settling Tank (CST) tool. Based on the blade obtained two results the percentage of oil content of 10.85%. This shows that there is still oil content in the mud. Likewise, the blade that found four pieces was 8.678%. While on the blade that got six pieces, the average percentage of oil was 7.652%. This shows that the blades that have been opened six pieces have met the desired percentage of oil standards.